Use of an interactive computer program for advance care planning with African American participants. Issue 2 (1st June 2012) - Levi, BH; Schubart, J; Markham, S; Whitehead, M; Farace, E; Lehmann, E; Green, MJ
Abstract : For various cultural and historical reasons, African Americans are less likely than Caucasians to engage in advance care planning (ACP) for healthcare decisions. This pilot study tested whether an interactive computer program could help overcome barriers to effective ACP among African Americans. African American adults were recruited from traditionally Black churches to complete an interactive computer program on ACP, pre-/post-questionnaires, and a follow-up phone interview. Participants were screened for cognitive ability, moderate/severe depression, and ≥8 th grade reading level. Eighteen adults (mean age = 53.2 years, 83% female) completed the program without any problems. Most participants (14/18) reported knowing "almost nothing" or "a little" about ACP prior to the study, and only 2 participants reported having previously created an advance directive. Knowledge about ACP significantly increased following the computer intervention (44.9% → 61.3%, p = 0.0004), as did individuals' sense of self-determination. Participants were highly satisfied with the ACP process (9.4; 1 = not at all satisfied, 10 = extremely satisfied), and reported that the computer-generated advance directive accurately reflected their wishes (6.4; 1 = not at all accurate, 7 = extremely accurate). Follow-up phone interviews found that most participants reported having shared their advance directives with family members (88%) and spokespeople (82%). Preliminary evidence suggests that an interactive computer program can help African Americans engage in effective advance care planning, including creating an accurate advance directive document that will be shared with loved ones.